(untitled) (Mustansiria Dental Journal, 2018)
Dental cement is one of few materials which have been developed specifically for dental use, most of the other dental materials have been borrowed from other environment and then modified to meet the particular requirements of dentistry (1). The zinc oxide eugenol is one of the most dental cement that is used as a base material beneath metallic dental restoration and as an insulating temporary filling material and cement temporary crown, it is required to improve the physical properties of zinc oxide eugenol in order to be superior than other cement, notably in respect of its palliative effect on the pulp so the addition of additives such as O –ethexy benzoic acid (EBA) and polystyrene may increase the strength of ZOE cement (2,3,4,5,6,7), such additives may have a deleterious effects on the film thickness and solubility (8,3,9) . Zinc oxide are mixed with eugenol the mix sets to a hard cement , it is supplied as a powder and liquid or two pasts system, Simple mixed of these plain tow materials harden in the mouth in about 12 hours (1) but did not have great strength when compared with other types of cements (11,12), An attempt to achieve a convenient setting time and strength of cement changing the ratio of base to accelerator has been advocate (6,7,13). So generally recognized or as a company suggestion to improve the handling and physical properties (hardness) of commonly used temporary ZOE cement by combining it with a mixture of semisolid saturated hydrocarbons lubricant of petroleum jelly (14). Aim of Study: Comparing (in-vitro) the hardness of Zinc Oxide Eugenol cement before and after adding different amount of Petroleum jelly.